Tsunami Risk Assessment on Public Facilities in Southern Part of Bantul Regency, Yogyakarta - Nurmaya Acintya; Suryo Herbanu Pranoto; Ma’rifatun Nisaa’ Ratri; ‘Arifati Azmiyatul; Alihusni Wardana Randy; Sahid; Andika Firmansyah Reosa; Yogo Yudhanti Fatah (E3S Web of Conferences, 2023)
The southern part of Java Island is susceptible to tsunamis as its role as a subduction zone between Indo-Australian and Eurasian plates. On July 17, 2006, a tsunami struck Java's south coast triggered by an earthquake and affected more than 300 km of shoreline, as well as claimed more than 730 casualties. It is important to assess the risk in the southern part of Java. This research aims to analyze tsunami risk assessments on public facilities in the southern part of Bantul Regency, Yogyakarta. The Tsunami hazard map was created by using tsunami modeling from BMKG. Public facilities footprint such as health facilities, religious facilities and school were derived from data provided by Open Street Map (OSM). The Papathoma Tsunami Vulnerability Assessment (PTVA) model, specifically developed to estimate the relative vulnerability of buildings to tsunami hazards, is used to generate a building vulnerability map. A geographic information system (GIS) was utilized to calculate and visualize the hazard, vulnerability, and risk map. A total of 394 buildings were analyzed with the results that public facilities in three sub-districts, namely Srandakan, Sanden and Kretek, had varying levels of building vulnerability ranging from minor, moderate, average and high with RVI values ranging from 1.5 to 3.4. Additionally, tsunami risk assessment of public facilities indicates that buildings within Bantul Regency are categorized as having very high, high, moderate, or low levels of building risk.